Peningkatan Keterampilan Berpikir Kritis dan Kolaborasi Mahasiswa Melalui Model Discovery Learning - Ekaputra, Firdiawan (Universitas Mathla'ul Anwar Banten, 2023)
This study aims to determine the improvement of critical thinking skills and student collaboration through practicum learning with the discovery learning model. The samples used in this study were students of the Jambi University Chemical Education Study Program who took the inorganic chemistry practicum course in the 2022/2023 academic year, class R-002 as the experimental class and class R-004 as the control class. This research is a type of experimental research with a quasi-experimental model. Research data regarding critical thinking skills and student collaboration were collected using a questionnaire. Data on critical thinking skills and collaboration were obtained twice, namely pretest and posttest. The data obtained were then analyzed using the manova test. The results obtained in this study are that there is an increase in critical thinking skills and student collaboration through practicum learning with a significant discovery learning model.